Nuclear and mitochondrial control of the apoptosis machinery regulates neural stem cell fate - Xavier, Joana Mafalda Rodrigues (2014)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2014